Efficiency Of The Drug Free Village (Village Program Shines In The City Of Semarang - Febriana, Anita; Yuniningsih, Tri; Putranti, Ika Riswanti (Universitas Pahlawan Tuanku Tambusai, 2024)
The Drug-Free Village program, known as